PDLIM2 a jeho role v onkogenezi--tumor supresor nebo onkoprotein? - Maryáš, J; Bouchal, P (Klinicka onkologie, 2015)
PDZ and LIM domain containing protein 2 (PDLIM2), also known as Mystique or SLIM, is a member of the actinin-associated LIM family of proteins that play essential roles in cytoskeletone organization, cell differentiation and have been associated with oncogenesis. PDLIM2 is cytoskeletal and nuclear protein encoded by the Mystique gene localized on chromosome 8p21. PDLIM2 regulates stability and activity of several transcription factors, e. g. NF κB or STAT, and its deregulation is associated with several malignancies. PDLIM2 expression has been connected with both tumor suppression and tumorigenesis. PDLIM2 levels are epigenetically suppressed in different cancers due to Mystique promoter hypermetylation that blocks its transcription. PDLIM2 re expression is able to inhibit tumorigenicity and induces tumor cell death both in vitro and in vivo, which suggest potential tumor suppressor role of PDLIM2. On the other hand, PDLIM2 is highly expressed in cancer cell lines derived from metastatic cancer and its expression is associated with tumor progression and metastasis formation, indicating pro oncogenic role of PDLIM2. The aim of this review is to summarize current knowledge on the role of PDLIM2 in tumor formation and development, focusing on its prospective role as therapeutic target and offering potential explanations of its different functions in oncogenesis that were identified so far.
Keywords: proteiny s doménou LIM; LIM Domain Proteins; karcinogeneze; mikrofilamentové proteiny; Carcinogenesis; Humans; lidé; promotorové oblasti (genetika); Promoter Regions, Genetic; Tumor Suppressor Proteins; Microfilament Proteins; DNA Methylation; metylace DNA; nádorové supresorové proteiny